Propuesta de enseñanza en Cálculo Vectorial: un acercamiento a la clase invertida - Rojas-Celis, Carolina; Cely-Rojas, Valeria (Revista Científica, 2020)
Low academic performance from engineering's students in a course of vector calculus showed us the possibility to design a proposal based on model of flipped classroom approach, which includes planning and elaboration of a textbook, videos, the use of virtual classrooms, activities in GeoGebra and questionnaires online. The objective of the research was to evaluate the change from a traditional teaching model to an inverted classroom model from a quantitative and qualitative point of view, with two Vector courses of vector calculus during the second semester of 2018. A class schedule was designed as a guide for the development of the topics. The results showed an improvement in the autonomous learning processes, a higher level of comprehension of subjects and a decrease in the percentage of loss of the course.